2012
DOI: 10.1063/1.4766589
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of complexities in combustion instability in a lean premixed gas-turbine model combustor

Abstract: Reduced hierarchy equations of motion approach with Drude plus Brownian spectral distribution: Probing electron transfer processes by means of two-dimensional correlation spectroscopy J. Chem. Phys. 137, 22A550 (2012) Rectified Brownian transport in corrugated channels: Fractional Brownian motion and Lévy flights J. Chem. Phys. 137, 174101 (2012) Brownian dynamics simulations with hard-body interactions: Spherical particles J. Chem. Phys. 137, 164108 (2012) Noncolliding Brownian motion with drift and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
54
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 110 publications
(60 citation statements)
references
References 54 publications
0
54
0
Order By: Relevance
“…For example, Gotoda et al 14 have observed variations of minimum permutation entropy 41 as a function of equivalence ratio È to detect the degree of complexity of pressure time series at the onset of combustion instability. They have also observed that the dynamic behavior in combustion instability near lean blowout exhibits a self-affine structure, which is ascribed to fractional Brownian motion and undergoes chaos by the onset of combustion oscillations with slow amplitude modulation.…”
Section: Instability Prediction By D-markov and âD-markov Entropy Ratesmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, Gotoda et al 14 have observed variations of minimum permutation entropy 41 as a function of equivalence ratio È to detect the degree of complexity of pressure time series at the onset of combustion instability. They have also observed that the dynamic behavior in combustion instability near lean blowout exhibits a self-affine structure, which is ascribed to fractional Brownian motion and undergoes chaos by the onset of combustion oscillations with slow amplitude modulation.…”
Section: Instability Prediction By D-markov and âD-markov Entropy Ratesmentioning
confidence: 99%
“…time series, which varies linearly with data length. The minimum permutation entropy is obtained by (multiple times with varying order) usage of a fast window-based algorithm 43 on pressure data that are downsampled to 5 kHz with an embedding delay of 1 ms similar to Gotoda et al 14 The time complexity for computation of both Hurst exponent 9 and ÂD-Markov entropy rate (see Instability prediction by D-Markov and ÂD-Markov entropy rates subsection) vary linearly with data length and have very small slopes. The mean of the Hurst exponent of order 2 is estimated here with a range of time scales ranging from 15 ms to 30 ms (i.e.…”
Section: Instability Prediction By D-markov and âD-markov Entropy Ratesmentioning
confidence: 99%
See 1 more Smart Citation
“…The dynamics of a combustor close to blowout is a topic of intense current research. For example, Gotoda and coworkers [17] [18] 224…”
Section: B Reduction Of Modeling Complexity Near Lean Blowoutmentioning
confidence: 99%
“…Kabiraj et al [15] and Kabiraj and Sujith [16] investigated dynamics of a ducted laminar premixed flame and using tools of dynamical systems analysis demonstrated that the system undergoes a number of bifurcations involving quasiperiodic and intermittent behaviors leading to blowout. Gotoda and co-workers [17] used a number of analytical tools to examine the dynamics of a model gas turbine combustor and showed that close to lean blowout the dynamics of the combustor exhibits a self-affine structure indicating fractional Brownian motion but changes to chaotic oscillations showing oscillations with slow amplitude modulation as the equivalence ratio increases. Gotoda et al [18] showed that the relatively regular pressure oscillations undergo transition to intermittent chaotic oscillations as the equivalence ratio is decreased and the system approaches LBO.…”
Section: Introductionmentioning
confidence: 99%